Religiosity as a moderator on business success: A campaign for open innovation - Aziz, Ahmad Amir; Fitriyah, Any Tsalasatul (Faculty of Economics and Business, University of Muhammadiyah Malang, 2024)
The study investigates how managerial competency (MC) and entrepreneurial orientation (EO) impact the business success (BS) of small and medium enterprises (SMEs) in the food sector, with an examination of religiosity as a moderating factor. Purposive sampling was employed to select a sample of 122 owners and workers from culinary businesses on Lombok Island, Indonesia. Data analysis was conducted using Structural Equation Modeling (SEM) with AMOS 22. The findings underscore MC's critical role in enhancing BS, alongside EO's significant influence on overall company performance. Moreover, the study reveals that religiosity plays a moderating role in shaping the relationships between MC, EO, and BS. Furthermore, our research connects these insights to the concept of open innovation. By integrating aspects of religiosity into the implementation of open innovation in SMEs, not only can the quality of innovation be enhanced, but it can also cultivate a positive reputation that contributes to increased business success.